Physicochemical properties of corn flour modified by mixed-culture (Aspergillus sp. and Lactobacillus fabifermentans) fermentation - Sukainah, Andi; Putra, Reski Praja; Tawakal, Intan Syafinaz Mohamen Amin; Fadilah, Ratnawaty (jurnal1, 2025)
Corn flour has undergone numerous modifications, however, the use of fermentation with Indigenous mixed cultures (molds and bacteria) followed by pregelatinization has not been extensively explored. The aim of the study was to assess the impact of fermentation with indigenous mixed cultures, specifically Aspergillus sp. (AS) and Lactobacillus fabifermentans (LF), on the physicochemical properties of modified corn flour, as well as its application in product quality. Corn flour was fermented using mixed cultures of AS and LF in a Complete Random Design (CRD) at five different ratios (AS: LF) of 1:0, 1:1, 1:2, 1:3, and 0:1. Each culture was incubated for 120 hours for AS and 48 hours for LF, then diluted by mixing 1 mL of the culture with 10 mL of sterile water. This diluted solution (according ratio) was aseptically added to a sterile corn flour dispersion at a ratio of 1:2 (w/v) and fermented under microaerophilic conditions for 48 hours. The fermented dispersions were dried and subsequently steamed (80°C) for 15 minutes at a 30% (w/v) ratio to prepare samples for analysis of amylose content, starch content, pasting, and rheological properties. The optimal AS: LF ratio determined through statistical analysis was 1:3, resulting in a final pH of 3.60 ± 0.10. The physicochemical properties of the corresponding steamed samples were as follows: amylose content (%), 17.45 ± 0.62; starch content (%), 68.94 ± 0.69; apparent consistency index (cP), 25,286 ± 512.9; and apparent power-law index, 0.32 ± 0.005, indicating pseudoplastic rheological behavior. The modified corn flour (AS: LF at 1:3) was then used in a 50% formulation for making bread and noodles. The resulting products showed potential for larger-scale development.